Evaluating The Glycolytic Shifts In Respiratory Diseases: A Correlative Study - Johnson, Jesbin; Kumar, Manoj; Yadav, Ashok; Chandel, Neha; Bharti , Jaya; Garima, Garima (Journal of Neonatal Surgery, 2025)
Objective: To examine the possible correlation between the glycolytic profile which include glucose and lactate level in various respiratory condition like asthma, pneumonia, cystic fibrosis, tuberculosis etc. Result: A study examining the relationship between glucose and lactate levels among 100 patients with respiratory conditions found considerable variability in glucose levels and lactate levels. Elevated glucose levels were observed in some patients, while normal ranges were 70-99 mg/dL (fasting) or up to 125 mg/dL (non-fasting). A weak positive linear association was found, suggesting a slight rise in lactate levels as glucose levels rose. Fisher's z-transformation showed a 95% confidence interval for the correlation coefficient, suggesting a minimal and clinically not relevant correlation. A scatter plot showed no obvious trend, indicating that elevated glucose levels may be an accurate measure of lactate buildup. Novelty: In order to provide insight into metabolic adaptations and the impact of variables such as medicine, lifestyle choices, and the severity of the disease on glucose and lactate levels, this study investigates the weak relationship between glucose and lactate metabolism in respiratory patients.